To disclose or not: experiences of HIV infected pregnant women in disclosing their HIV status to their male sexual partners in Blantyre, Malawi - Annie Kalibwe Mkandawire; Vincent Jumbe; Alinane Linda Nyondo-Mipando (BMC Public Health, 2022)
Abstract Background HIV status disclosure is one of the pillars of success of the elimination of Mother to Child Transmission of HIV (eMTCT) program. However, there are challenges associated with it that limit full disclosure. Literature shows that for pregnant women in developing countries, who have been diagnosed with HIV, 16% to 86% disclose their status to their sexual partners. This study explored the experiences of newly diagnosed HIV-infected antenatal women in disclosing their HIV status to their male sexual partners in Blantyre, Malawi. Methods This was a qualitative explanatory multiple case study that was conducted from 2018 to 2019 using in-depth interviews and diaries as data collection tools. We recruited seven newly diagnosed HIV pregnant women who had not disclosed their status to their male sexual partners and were initiated on Option B + strategy of the eMTCT of HIV at Limbe Health Centre. The investigator had 3 contacts with each participant from which data was gathered except for one participant who got lost to follow-up. This study employed content analysis and used a within-case and across-case analysis. Results Women either use facilitated mutual disclosure process or disclosed directly to their male sexual partners. Women were motivated to disclose because they wanted an HIV-free baby, to know the partners' status, and to resolve the gap on how they got infected with HIV. The disclosure process faced challenges such as uncertainty about a partner’s reaction after disclosure, fear of relationship dissolution, and the soberness of the partner. Privacy was an important consideration during the process of disclosure. Following disclosure, male sexual partners either accepted the status immediately after disclosure or initially denied but later accepted. Conclusion This study has shown that newly diagnosed HIV pregnant women accessing eMTCT services have a plan of either to disclose or conceal their HIV status from their male sexual partner and this decision is affected by the nature of relationship that exist between them and their partner. Factors relating to the unborn baby, the relationship as well as to know partners status motivate women to either disclose or conceal.